The Influence of Social Media Marketing on Purchase Decisions: Exploring the Mediating Effects of Promotion and Customer Experience - Zahra Nur Aninda; Rifky Roosdhani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Businesses must use social media if they want to survive in this modern era. Almost all industries need social media to increase market share, boost brand credibility, and increase customer trust. Social media is also necessary for the transportation industry to function properly. Until now, there has not been much research on transportation related to marketing activities on social media, especially buses. This study provides a new perspective on efforts to improve SMMA purchasing decisions. It was found that customer experience and promotion variables are necessary as mediating variables between SMMA and purchase decisions. This study collects and analyzes quantitative data. In this study, purposive sampling method was used to 506 sample bus passengers at PO Bejeu Jepara. The empirical model was tested with Smart PLS 4.0 software.